Islamisasi Ilmu Pengetahuan Menurut Pemikiran Ismail Raji Al-Faruqi dan Syad Naquib Al-Attas - Devi Elsi Susanti; Muhammad Zalnur; Fauza Masyhudi (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2025)
Islamization emerged because of the concerns of Muslim intellectuals who saw that Muslims were in crisis due to the application of secular-based Western science. The secular concept of science is not suitable for Muslims because it separates religion from science. So far, Islam is believed to have a very important role in coloring the building of science. However, in reality, Muslim society seems to be forced to implement secular teachings in life because of the rapid flow of secularization. This condition is a concern for Islamic thinkers, because it could endanger Islamic faith. Thus, a critical opinion emerged from a Muslim scholar who came up with the idea of ​​the Islamization of science, namely Ismail Raji Al-Faruqi and Syad Naquib Al-Attas. Both of them saw that the phenomenon of scientific development had deviated from Islamic teachings. So that it has the impact of someone becoming secular. This research aims to discuss the Islamization of science according to the thoughts of Ismail Raji Al-Faruqi and Syad Naquib Al-Attas. The method used in this research is a research library, by collecting previous articles and sources. The results of this research reveal that Al-Faruqi and Al-Attas have similarities in their thinking, namely that they both think that the main problem of the Muslim crisis is science developed by the West.